RE: GITR GENE DELETION AND GITR-FC SOLUBLE PROTEIN ADMINISTRATION INHIBIT MULTIPLE ORGAN FAILURE INDUCED BY ZYMOSAN. DOI: 10.1097/SHK.0B013E3182262C48 - Salvatore Cuzzocrea (Shock, 2024)
Online social media discussions offer insight into patient experiences with refractive and cataract surgery. This retrospective cross-sectional study analyzed 1000 recent posts from Reddit communities (r/lasik, r/cataractsurgery), of which 931 met inclusion criteria. Posts were categorized by content and analyzed for sentiment using the VADER tool. Most posts were patient-authored (96.5%) and question-based (59.0%), with cataract surgery (27.1%), LASIK (20.4%), and PRK (11.7%) most frequently discussed. Postoperative topics predominated (75.7%), particularly quality of life, need for additional visual correction, and side effects. Overall sentiment was positive (median compound score 0.49), with significant variation by topic and procedure (p<0.001), including lower sentiment in cataract-related discussions. Treatment anxiety was more common in non-cataract refractive procedures, often driven by conflicting information from multiple sources. These findings suggest that social media serves as a supplementary source of perioperative guidance while highlighting persistent uncertainty regarding visual outcomes, refractive procedure differences, and lens selection.